NEXIUM. PREVENTION OF GASTRODUODENAL ULCER ASSOCIATED WITH NONSTEROIDAL ANTI-INFLAMMATORY DRUGS (Рациональная фармакотерапия в кардиологии, 2015)
Nexium. Prevention of gastroduodenal ulcer associated with nonsteroidal anti-inflammatory drugs.